Analisis Implementasi Standar Nasional Perpustakaan Sekolah Menengah Atas/Madrasah Aliyah (SNP 12:2017) - Moh Suhri Rohmansyah; Hanafi Hanafi (Studia Manageria, 2022)
This study aims to find out how SNP 12:2017 is implemented in the SMAN 6 Pandeglang Library. This type of research is descriptive with a qualitative approach. Data collection techniques in this study are observation, interviews, literature review, and documentation. The results of this study are as follows: first, SNP 12:2017 has seven standards, namely collection standards, infrastructure standards, service standards, library staff standards, implementation standards, management standards, and information technology standards. For librarians in the SMAN 6 Pandeglang library who have the academic competence of library education graduates, the SMAN 6 Pandeglang library only has one room for various library areas. There is a lack of administrators and librarians in the SMAN 6 Pandeglang library who have competence in the field of information technology. Third, the factors that support the implementation of SNP 12:2017 are complete facilities and infrastructure, sufficient time for service activities, and additions to collections carried out every year. Fourth, the process and level of achievement of SNP 12:2017 are not fully implemented and in accordance with SNP 12:2017. There are several aspects that have started to reach SNP 12:2017, including service aspects, implementation aspects, management aspects, and several other aspects. As well, there are several aspects that have not reached SNP 12:2017, including aspects of collection, aspects of information and communication technology, aspects of facilities and infrastructure, and several other aspects.